الإحتراق النفسي لدى معلمات مدارس التربية الخاصة بمدينة طرابلس - غلام، عيسى حسن عمر; القاضي، نجاة أحمد Alqadi, Najah Ahmed (جامعة بنغازي - كلية التربية, 2018)
هدفت الدراسة للتعرف على مستوى الاحتراق النفسي لدى معلمات مدارس التربية الخاصة بمدينة طرابلس من وجهة نظر أفراد العينة والتعرف على الفروق ذات الدلالة الإحصائية في مستوى الاحتراق النفسي لدى معلمات مدارس التربية الخاصة ترجع لمتغيرات (المدرسة، المؤهل العلمي، مدة الخدمة)، ولتحقيق أهدافها قام الباحثان بإجراء دراسة ميدانية بمؤسستي الأمل لضعاف السمع ومركز تنمية القدرات الذهنية جنزور من خلالها توصلا لعدة نتائج أهمها: مستوى الاحتراق النفسي لدى المعلمات في مؤسستي (الأمل لضعاف السمع سوق الجمعة طرابلس ومركز تنمية القدرات الذهنية جنزور) بمدينة طرابلس كان عاليا، لا توجد فروق ذات دلالة إحصائية في مستوى الاحتراق النفسي لدى المعلمات في مؤسستي (الأمل لضعاف السمع سوق الجمعة طرابلس ومركز تنمية القدرات الذهنية جنزور) بمدينة طرابلس ترجع لمتغير المدرسة. لا توجد فروق ذات دلالة إحصائية في مستوى الاحتراق النفسي لدى المعلمات في مؤسستي (الأمل لضعاف السمع سوق الجمعة طرابلس ومركز تنمية القدرات الذهنية جنزور) بمدينة طرابلس ترجع لمتغير المؤهل العلمي، لا توجد فروق ذات دلالة إحصائية في مستوى الاحتراق النفسي لدى المعلمات في مؤسستي (الأمل لضعاف السمع سوق الجمعة طرابلس ومركز تنمية القدرات الذهنية جنزور) الخاصة بمدينة طرابلس ترجع لمتغير مدة الخدمة. The study is aiming at identifying the level of psychological burnout among teachers of Private Education schools in Tripoli from the point of view of the sample members and identifying the differences of statistical significance in the level of psychological burnout among teachers. Such condition is due to variables like (school, qualification, duration of service). To achieve this objective the two researchers carried a filed study in Al-amal institution for the impaired hearing and the Janzour Center for Mental Capacity Development. This study revealed that the level of psychological burnout among female teachers in the two institutions (Al-amal for the impaired hearing at Souk Al-Joumaa and the Janzour Center for Mental Capacity Development) in the city of Tripoli was higher. There are no differences that are statistically significant in the level of psychological burnout among female teachers of the two institutions (Al-amal for the impaired hearing at Souk Al-Joumaa and the Janzour Center for Mental Capacity Development) in the city of Tripoli due to the school variable. There are no statistically significant differences in the level of psychological burnout among female teachers of the two institutions (Al-amal for the impaired hearing at Souk Al-Joumaa and the Janzour Center for Mental Capacity Development) in the city of Tripoli due to the qualification variable, There are no statistically significant differences in the level of psychological burnout among female teachers of the two institutions (Al-amal for the impaired hearing at Souk Al-Joumaa and the Janzour Center for Mental Capacity Development ) in the city of Tripoli due to the qualification variable.
Keywords: الصحة النفسية -- الإحتراق النفسي -- التربية الخاصة -- معلمات التربية الخاصة -- مدينة طرابلس